BS EN ISO 12736-3. Petroleum and natural gas industries. Wet thermal insulation systems for pipelines and subsea equipment. Part 3. Interfaces between systems, field joint system, field repairs and prefabricated insulation (20th December 2021) - British Standards Institution,
No abstract available